2010
DOI: 10.1021/bc100115m
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton-Absorption-Induced-Luminescence (MAIL) Imaging of Tumor-Targeted Gold Nanoparticles

Abstract: We demonstrate that multiphoton-absorption-induced luminescence (MAIL) is an effective means of monitoring the uptake of targeted nanoparticles into cells. Gold nanoparticles (AuNPs) with diameters of 4.5 and 16 nm were surface-functionalized with monocyclic RGDfK, an RGD peptide analogue that specifically targets the α(v)β₃ integrin, a membrane protein that is highly overexpressed in activated endothelial cells during tumor angiogenesis. To determine whether cyclic RGD can enhance the uptake of the functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…[23][24][25] Based on this, we developed a method to detect AuNP in skin. 8,26,28 Though multiphoton microscopy is a nondestructive optical technique, skin sectioning was required to avoid the possible limitations when imaging from the top view in case of nonsectioned skin specimens in which AuNP could be detected up to variable depths from the skin surface ranging from 14 to 100 μm, depending on skin pre-treatment (tissue fixation) and area of examination (presence or absence of wrinkles).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] Based on this, we developed a method to detect AuNP in skin. 8,26,28 Though multiphoton microscopy is a nondestructive optical technique, skin sectioning was required to avoid the possible limitations when imaging from the top view in case of nonsectioned skin specimens in which AuNP could be detected up to variable depths from the skin surface ranging from 14 to 100 μm, depending on skin pre-treatment (tissue fixation) and area of examination (presence or absence of wrinkles).…”
Section: Resultsmentioning
confidence: 99%
“…This technique is referred to as multiphoton-absorption-induced luminescence (MAIL), where the absorption of multiple photons from a near-infrared pulsed femtosecond laser can lead to robust luminescence of metal nanoparticles. 8,[23][24][25][26] Multiphoton microscopy was therefore employed as a useful optical technique to track particle penetration in skin 8,22,[26][27][28] and was the imaging tool in our study to track model AuNP.…”
Section: Introductionmentioning
confidence: 99%
“…There are two major classes of nanomaterials that have a good multiphoton absorption cross-section: QDs and metallic nanoparticles. For example, different sizes of gold nanoparticles conjugated with RGD peptide can generate distinct multiphoton absorption-induced luminescence (MAIL) signals under 800 nm [72]. This surfacefunctionalized nanostructure was found to have an ability to target tumor cells and to give transmission images via MAIL.…”
Section: Organic-inorganic Nanohybrids For Photoacoustic and Multiphomentioning
confidence: 99%
“…[1, 12, 13, 14, 15, 16] It has been demonstrated that Multiphoton-Absorption-Induced Luminescence from gold NPs is efficiently generated using a 2-photon excitation source at 800 nm with excitation intensities that are lower than those typically used for 2-photon imaging of living cells. [1] 25 years ago, Boyd and co-workers showed that gold surfaces exhibit ~100 times more luminescence when irradiated with a 2-photon excitation source compared to 1-photon excitation.…”
Section: Introductionmentioning
confidence: 99%